Formulation of Underage Marriage in The Perspective of Islamic Law and Legal Sociology - Humaeroh; Zakaria Syafei; Nurul Ma’rifah (KRTHA BHAYANGKARA, 2023)
The child's independence in pursuing ideals and realizing success for the future is a desire for parents and the country. This can be achieved when the child has carried out a good learning process that can be taken through the formal or informal level. However, the irony that occurs if a child's dream of becoming a person is useful for the future, religion, and the state must be cut off with what happens, such as marriages that are still not on time or underage marriages.  This research aims to analyze underage marriages from the perspective of Islamic law and understand the benchmarks of legal awareness in society to minimize the occurrence of underage marriages and to know the implications of underage marriages. This study is library research using a qualitative approach.  The results show that Marriage is a strong bond or mitsqon golidhon carried out by couples who have met the age limit or baligh, but marriages, carried out by someone who is underage must be based on a recommendation through a marriage dispensation issued by a religious court. Second, community indicators in realizing legal knowledge and understanding will form a stable legal attitude so that they can apply patterns of legal behavior. Third, the implications of underage marriage include the disruption of compulsory education, Fulfillment of subsistence, which is not optimal for the families, diversion of responsibility to parents because they have not been able to work properly, Reproductive health conditions are still vulnerable due to lack of good nutrition and give rise to poverty and vulnerability to divorce.